Enhancing the quality of life through wearable technology. - Sungmee Park
An overview of the key challenges facing the practice of medicine today is presented along with the need for technological solutions that can "prevent" problems. Then, the development of the Wearable Motherboard? (Smart Shirt) as a platform for sensors and monitoring devices that can unobtrusively monitor the health and well being of individuals (directly and/or remotely) is described. This is followed by a discussion of the applications and impact of this technology in the continuum of life-from preventing SIDS to facilitating independent living for senior citizens. Finally, the future advancements in the area of wearable, yet comfortable, systems that can continue the transformation of healthcare - all aimed at enhancing the quality of life for humans - are presented.
Keywords: SIDS; Smart Shirt; Wearable Motherboard; Health monitoring; Independent living; Monitoring devices; Personalized wearable intelligent information infrastructure; Quality of life; Senior citizens; Sensors; Wearable technology; Well being monitoring